Corporate law and corporate psychopaths. Issue 4 (4th July 2021) - Sheehy, Benedict; Boddy, Clive; Murphy, Brendon
Abstract : For more than three decades there has been a growing interest, and concern, in the role that psychopathy plays in corporate affairs. The literature in this field is essentially interdisciplinary, drawing heavily on advances in neuroscience, behavioural and organisational psychology and criminology. In this paper, the authors open a line of enquiry on the role that law can play in the regulation, and remedies, available to deal with dysfunctional and psychopathic management. In this paper we argue that the impact of corporate psychopaths – particularly the sub-clinical types – is sometimes potentially devastating for the organisation, its mission, its employees and, where they exist, shareholders. In this article we outline the nature of corporate psychopathy and its impact on corporate entities and outline a range of potential legal remedies.